The Income Tax Policy for Freelancers in Indonesia and Malaysia’s Creative and Gig Economies - Zahroh, Fatmawati; Mardiana; Kamis, Jamilah (JAS (Jurnal Akuntansi Syariah), 2025)
The paper investigates fiscal policy in response to the growth of creative and gig economy by investigating the income tax treatment on a freelance workers in Indonesia and Malaysia. The aim of the study is to assess how current income tax rules capture non-standard employment and to compare the adequacy, equity and administrative complexity of both countries responses. The analysis is based on a comparative qualitative legal methodology, where the doctrinal legal analysis of tax laws and regulations has been combined with the review of policy papers, official guidelines and secondary literature on taxation in gig economy. The tax base determination, compliance measures, withholding systems and government support tools for freelancers are assessed applying a comparative template. These findings show that Indonesia uses self-assessment with simplified norms more than Malaysia for selected freelancers, whereas Malaysia it has more transparent classification and schedule income treatment, along with stronger withholding and digital reporting systems. Both systems experience some compliance cost, income volatility and enforcement issues in platform work but Malaysia has greater administrative certainty. Theoretically, the study suggests that adaptive tax systems are needed to adapt with changing labor market structures whereas practically, policymakers need to work on protection of legal safety, simplification and compliance and digital tax administrations in order for gig economy to be subjected fair and sustainable revenues.